Working Class Lifestyle in Saturday Night and Sunday Morning by Alan Sillitoe - Groh, Lubomír (Univerzita Pardubice, 2013)
The main aim of this bachelor thesis is to analyse the novel Saturday Night and Sunday Morning by Alan Sillitoe. The first part of the thesis provides a description of the situation in Britain after the Second World War along with a characterization of the literary movement Angry Young Men. The second part of the paper is focused on analysing elements of individualism as well as on discussing the living conditions depicted in the book. This part closes with the analysis of how this work influenced British culture.
Životní styl dělnické třídy v díle Sobotní noc a nedělní ráno od Alana Sillitoea
Keywords: Sillitoe, Alan; Sobotní noc a nedělní ráno; rozhněvaní mladí muži; individualismus; životní podmínky; Saturday Night and Sunday Morning; Angry Young Men; individualism; living conditions